Agricultural Performances of Some Safflower (Carthamus tinctorius L.) Lines Developed by Single Plant Selection Method - Arzu Köse; Özlem Bilir; Ferda Koşar (Journal of Agricultural Sciences)
This study was carried out to determine seed and oil yield with their components of some safflower lines and varieties under Eskisehir ecological conditions. This research was conducted at the experimental fields of Transitional Zone Agricultural Research Institute (TZARI), during 2010, 2011 and 2012. Both twenty-one safflower lines and four varieties (Yenice, Dincer, Remzibey and Balci) originating from TZARI-Eskisehir were evaluated in this research. The lines used in this study are developed by using single plant selection method. Three years data were collected and analyzed according to randomized block design with three replications. Means of seed yield, number of head per plant, head diameter, 1000 seed weight, oil content, oil yield were found 1330.3-1990.9 and 1210.1 kg ha-1, 11.2-12.3 and 9.6 number plant-1, 2.28-2.42 and 2.54 cm, 41.6-45.7 and 44.1 g, 36.1-36.6 and 35.6%, 470.9-730.0 and 430.0 kg ha-1 in 2010, 2011 and 2012, respectively. According to all years and combined analysis results of this study, lines GE-ESYA-36-36, GE-ES-YA-36-7 in terms of seed yield, lines GE-ES-YA-36-30, GE-ES-YA-36-25, GE-ES-YA-36-26, GEES-YA-36-27 in terms of oil content and lines GE-ES-YA-36-36, GE-ES-YA-36-7, GE-ES-YA-36-4 terms of oil yield were listed at the highest statistical group. As a result of this study, it was decided that these lines could be candidate varieties with regard to these different characteristics.